Phenotypic and Genotypic Consequences of CRISPR/Cas9 Editing of the Replication Origins in the rDNA of Saccharomyces cerevisiae. Issue 1 (1st September 2019) - Sanchez, Joseph C; Ollodart, Anja; Large, Christopher R L; Clough, Courtnee; Alvino, Gina M; Tsuchiya, Mitsuhiro; Crane, Matthew; Kwan, Elizabeth X; Kaeberlein, Matt; Dunham, Maitreya J; Raghuraman, M K; Brewer, Bonita J
Abstract: The complex structure and repetitive nature of eukaryotic ribosomal DNA (rDNA) is a challenge for genome assembly, thus the consequences of sequence variation in rDNA remain unexplored. However, renewed interest in the role that rDNA variation may play in diverse cellular functions, aside from ribosome production, highlights the need for a method that would permit genetic manipulation of the rDNA. Here, we describe a clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9-based strategy to edit the rDNA locus in the budding yeast Saccharomyces cerevisiae, developed independently but similar to one developed by others. Using this approach, we modified the endogenous rDNA origin of replication in each repeat by deleting or replacing its consensus sequence. We characterized the transformants that have successfully modified their rDNA locus and propose a mechanism for how CRISPR/Cas9-mediated editing of the rDNA occurs. In addition, we carried out extended growth and life span experiments to investigate the long-term consequences that altering the rDNA origin of replication have on cellular health. We find that long-term growth of the edited clones results in faster-growing suppressors that have acquired segmental aneusomy of the rDNA-containing region of chromosome XII or aneuploidy of chromosomes XII, II, or IV. Furthermore, we find that all edited isolates suffer a reduced life span, irrespective of their levels of extrachromosomal rDNA circles. Our work demonstrates that it is possible to quickly, efficiently, and homogeneously edit the rDNA origin via CRISPR/Cas9.